2010
DOI: 10.1080/09658210902992917
|View full text |Cite
|
Sign up to set email alerts
|

Silence and the shaping of memory: How distracted listeners affect speakers' subsequent recall of a computer game experience

Abstract: The present study focused on how distracted listening affects subsequent memory for narrated events. Undergraduate students experienced a computer game in the lab and talked about it with either a responsive or distracted friend. One month later, those who initially spoke with distracted listeners showed lower retention of information about the computer game, and their subsequent memories were also less consistent with their initial conversational recall. Differences in subsequent memory across initial listene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…When listeners provided feedback, speakers changed their narrative in response; speakers elaborated their narrative to answer questions asked by the listener. Further, disclosing an experience to a distracted, as opposed to an attentive listener has been associated with the speaker creating narratives deficient in emotional and psychological aspects of the experience, which in itself can influence later memory accuracy for the original experience (Pasupathi & Hoyt, 2010). Thus, the presence and responsiveness of a listener during social disclosure can influence the content of the verbal narrative created by the speaker.…”
Section: The Presence and Behaviour Of A Listenermentioning
confidence: 99%
“…When listeners provided feedback, speakers changed their narrative in response; speakers elaborated their narrative to answer questions asked by the listener. Further, disclosing an experience to a distracted, as opposed to an attentive listener has been associated with the speaker creating narratives deficient in emotional and psychological aspects of the experience, which in itself can influence later memory accuracy for the original experience (Pasupathi & Hoyt, 2010). Thus, the presence and responsiveness of a listener during social disclosure can influence the content of the verbal narrative created by the speaker.…”
Section: The Presence and Behaviour Of A Listenermentioning
confidence: 99%
“…In this respect, each of the narrative examples discussed above can be thought of as the way in which a youth constructed her or his sense of moral agency vis-à-vis a certain event at a given point in time. And although, in general, the ways in which people initially narrate an event shapes and constrains how they will remember and understand that event, and what they will come to believe about themselves in relation to it, the retelling of experiences can also become an avenue for change [McAdams, 1993;Pasupathi, 2001;Pasupathi & Hoyt, 2010;Weeks & Pasupathi, 2011]. Different instances of talking about a certain event have the power to make people rethink themselves, and not merely for defensive or presentational purposes, but rather because this is the way that people construct, reflect on, refine, and reconstruct a sense of their own moral agency in relation to complicated events.…”
Section: Directions For Future Research and Interventionmentioning
confidence: 99%
“…In our own work, we have focused on the implications of distracted listening, compared with normal attentive listening, for current and later memories (Pasupathi, 2001;Pasupathi & Hoyt, 2010;Pasupathi, Stallworth, & Murdoch, 1998). In general, we have found that speakers faced with unresponsive listeners produce shorter memories that (1) are bereft of previously unrehearsed information (Pasupathi et al, 1998); (2) lack subjective content important for conveying what the experience means to the narrator (Pasupathi et al, 1998;Pasupathi & Hoyt, 2009);and (3) lack schematic content that might render an experience easier to recall in the future (Pasupathi & Hoyt, 2010).…”
mentioning
confidence: 99%
“…In general, we have found that speakers faced with unresponsive listeners produce shorter memories that (1) are bereft of previously unrehearsed information (Pasupathi et al, 1998); (2) lack subjective content important for conveying what the experience means to the narrator (Pasupathi et al, 1998;Pasupathi & Hoyt, 2009);and (3) lack schematic content that might render an experience easier to recall in the future (Pasupathi & Hoyt, 2010). Thus, it is not surprising that memories told to an unresponsive listener are less well retained on subsequent occasions than are memories told to an attentive listener (Pasupathi & Hoyt, 2010;Pasupathi et al, 1998). Additionally, subsequent memory for experiences narrated to attentive listeners was more consistent with the narrated version of the memory, as compared with later memories of experiences narrated to distracted listeners.…”
mentioning
confidence: 99%